Structures of Gating Intermediates in a K+ channel. Issue 23 (19th November 2021) - Reddi, Ravikumar; Matulef, Kimberly; Riederer, Erika; Moenne-Loccoz, Pierre; Valiyaveetil, Francis I.
Graphical abstract: Highlights: Ion flux through a K + channel is regulated by channel activation and inactivation. W67F in KcsA prevents inactivation and alters pH activation. Structures of KcsA W67F determined in the pre-open and the pre-inactivated state. Ion binding at second ion site in the selectivity filter required for inactivation. Insights into the allosteric pathway coupling activation and inactivation in KcsA. Abstract: Regulation of ion conduction through the pore of a K + channel takes place through the coordinated action of the activation gate at the bundle crossing of the inner helices and the inactivation gate located at the selectivity filter. The mechanism of allosteric coupling of these gates is of key interest. Here we report new insights into this allosteric coupling mechanism from studies on a W67F mutant of the KcsA channel. W67 is in the pore helix and is highly conserved in K + channels. The KcsA W67F channel shows severely reduced inactivation and an enhanced rate of activation. We use continuous wave EPR spectroscopy to establish that the KcsA W67F channel shows an altered pH dependence of activation. Structural studies on the W67F channel provide the structures of two intermediate states: a pre- open state and a pre-inactivated state of the KcsA channel. These structures highlight key nodes in the allosteric pathway. The structure of the KcsA W67F channel with the activation gate open shows altered ion occupancy at the second ion binding site (S2) in the selectivity filter. This finding in combination with previous studies strongly support a requirement for ion occupancy at the S2 site for the channel to inactivate.